Sporopollenin Microcapsule: Sunscreen Delivery System with Photoprotective Properties - Silvia Tampucci; Giorgio Tofani; Patrizia Chetoni; Mariacristina Di Gangi; Andrea Mezzetta; Valentina Paganini; Susi Burgalassi; Christian Silvio Pomelli; Daniela Monti (MDPI AG, 2022)
In recent years, the demand for high-quality solar products that combine high efficacy with environmentally friendly characteristics has increased. Among the coral-safe sunscreens, ethylhexyl triazone (Uvinul® T150) is an effective organic UVB filter, photostable and practically insoluble in water, therefore difficult to be formulated in water-based products. Oil-free sunscreens are considered ideal for most skin types, as they are not comedogenic and do not leave the skin feeling greasy. Recent studies reported that pollen grains might represent innovative drug delivery systems for their ability to encapsulate and release active ingredients in a controlled manner. Before being used, the pollen grains must be treated to remove cellular material and biomolecules, which could cause allergic reactions in predisposed subjects; the obtained hollow structures possess uniform diameter and a rigid wall with openings that allow them to be filled with bioactive substances. In the present work, pollen from Lycopodium clavatum has been investigated both as a delivery system for ethylhexyl triazone and as an active ingredient by evaluating its photoprotective capacity. The goal is to obtain environmentally friendly solar aqueous formulations that take advantage of both sunscreen and sporopollenin microcapsules' UV protection with a relatively low cost, as these pollen grains are widely available.